Balancing Community and Individual Health Efforts by Utilizing Sub-Primary Health Care at Regions: Analysis for Policy - Budi, Rocky Setya; Adisasmito, Wiku Bakti Bawono; Bachtiar, Adang; Rosanti, Elvi (UI Scholars Hub, 2024)
Public Health Centers (PHCs) are responsible for organizing public health efforts and individual health efforts. PHCs also serve as FKTP, UPTD, sub-district supervisors, and implementers of policies and programs from the Ministry of Health. The workload of PHCs is increasing because people visit PHCs primarily for treatment, rather than seeking preventive measures to stay healthy. The PHCs have Sub-PHCs to lighten the workload of the PHCs, but there is no policy regulating Sub-PHCs to be used as FKTP. This research aims to analyze the policy of Balancing Community and Individual Health Efforts by utilizing Sub-PHCs such as FKTP. The research uses qualitative methods with a policy analysis process design, using primary data from in-depth interviews and FGDs with 14 informants and secondary data by reviewing documents. The research results indicate that PHCs have a heavy workload, and are more focused on medical services, and access to FKTP for communities in remote areas remains challenging. Sub-PHCs deserve to be used as FKTP on par with Pratama Clinics to increase community access to FKTP, particularly in areas with difficult geographical access, and to help lighten the workload of PHCs. It is recommended that the Ministry of Health conduct a policy analysis to support PHCs becoming FKTP, in line with the Minister of Health Regulation Number 43 of 2019, to change the role of the auxiliary health centers (Sub-PHCs) into FKTP.